Atypical Fractures are Mainly Subtrochanteric in Singapore and Diaphyseal in Sweden: A Cross‐Sectional Study. (15th June 2015) - Schilcher, Jörg; Howe, Tet Sen; Png, Meng Ai; Aspenberg, Per; Koh, Joyce SB
ABSTRACT We have previously noted a dichotomy in the location of atypical fractures along the femoral shaft in Swedish patients, and a mainly subtrochanteric location of atypical fractures in descriptions of patients from Singapore. These unexpected differences were now investigated by testing the following hypotheses in a cross‐sectional study: first, that there is a dichotomy also in Singapore; second, that the relation between subtrochanteric and diaphyseal location is different between the two countries; third, that the location is related to femoral bow. The previously published Swedish sample (n = 151) was re‐measured, and a new Singaporean sample (n = 75) was established. Both samples were based on radiographic classification of all femoral fractures in women above 55 years of age. The distance between the fracture line and the lesser trochanter was measured. Femoral bow was classified as present or absent on frontal radiographs. Frequency distribution of the measured distances was analyzed using the Bayesian information criterion to choose the best description of the observed variable distribution in terms of a compilation of normally distributed subgroups. The analysis showed a clear dichotomy of the fracture location: either subtrochanteric or diaphyseal. Subtrochanteric fractures comprised 48% of all fractures in Singapore, and 17% in Sweden (p = 0.0001). In Singapore, femoral bow was associated with more fractures in the diaphyseal subgroup (p = 0.0001). This was not seen in Sweden. A dichotomous location of atypical fractures was confirmed, because it was found also in Singapore. The fractures showed a different localization pattern in the two countries. This difference may be linked to anatomical variations, but might also be related to cultural differences between the two populations that influence physical activity. © 2015 American Society for Bone and Mineral Research